The structure of nasal conchae in Svalbard rock ptarmigan (Lagopus muta hyperborea) with comparisons to three other Galliform birds - Westvik, Marie Aas (UiT Norges arktiske universitet, 2022)
Birds are endothermic homeotherms that regulate internal metabolic heat production to keep a stable body core temperature. Lung ventilation, which is required to obtain oxygen for metabolism, is potentially a large source for heat and water loss. In a polar habitat with low year-round temperatures and scarcity of food in the winter, conservation of heat and water is crucial for survival of the resident Galliform bird Svalbard rock ptarmigan (Lagopus muta hyperborea). Nasal conchae are important for minimizing respiratory heat and water losses, a process known as nasal temporal countercurrent heat exchange (NHE). These are cartilaginous scroll-shaped and mucosa-lined structures protruding into the nasal cavity of birds. Heat and water conservation is assumed to be more important in species adapted to very cold or dry habitats, as conservation of the limiting resource is crucial for species survival in such habitats. More elaborate conchae would therefore be beneficial. Hence, I hypothesized that Svalbard rock ptarmigan, adapted to a polar habitat, have more elaborate nasal conchae than the domestic chicken (Gallus gallus domesticus), adapted to a temperate habitat, with mainland rock ptarmigan (Lagopus muta) and willow ptarmigan (Lagopus lagopus) being intermediate. To investigate this, head specimens of all study birds were obtained. Computed tomography (CT) scans of the heads were made, including histologic investigations of the nasal conchae in Svalbard rock ptarmigan. Finally, the potential importance of NHE in reducing respiratory heat loss in the Svalbard rock ptarmigan was estimated and compared to existing metabolic data. CT scans revealed that Svalbard rock and willow ptarmigan had larger conchal surface areas than the domestic chicken, the Svalbard rock ptarmigan having the largest conchal surface area of all study birds independent of body size differences. Scaled to volume of air space, the willow ptarmigan exceeded the Svalbard rock ptarmigan. 62.7 % of the heat added upon inhalation could be ...